Emotion regulation mediates relationships between perceived childhood invalidation, emotional reactivity, and emotional eating. (December 2021) - Braden, Abby; Anderson, LaNaya; Redondo, Rachel; Watford, Tanya; Emley, Elizabeth; Ferrell, Emily
Dialectical Behavior Therapy (DBT) is informed by the biosocial model which suggests that emotional sensitivity and childhood invalidation interact to influence emotion dysregulation, leading to behavioral disorders. Although adapted DBT interventions have resulted in improved emotional eating, little research has been conducted to examine whether key aspects of the biosocial model apply to emotional eating. Adults ( N = 258) were enrolled via Amazon's Mechanical Turk. Three separate mediation analyses were performed using Hayes' SPSS macro. Results showed that emotion regulation difficulties mediated the relationships between biosocial variables (i.e. perceived maternal and paternal invalidation and emotional reactivity) and emotional eating.